U.S.-China Trade War: Announcement Effects of Trump Tariff Cancellations on China’s Financial Firms - Tong, Xiaochuan; Lu-Andrews, Ran; Kunkel, Robert A. (Journal of Accounting and Finance, 2024)
The U.S.-China trade war was escalated in 2018 when the Trump administration announced a series of tariffs on Chinese products and services. In January 2018, President Trump imposed 30 percent and 20 percent tariffs on solar panels and washing machines. President Trump continued to impose more tariffs throughout 2018 and 2019. The Trump administration finally reversed course by announcing two Trump tariff cancellations in October 2019 and December 2019; thereby signaling a de-escalation in the U.S.-China trade war. We use an event study methodology to examine the announcement effects of those two Trump tariff cancellations on China’s publicly traded financial firms, including banks, insurance companies, and securities firms. We find the announcement effects are positive for China’s financial firms which experience a tremendous 5.60% cumulative abnormal return. In dollar terms, the mean market capitalization increase was $1.36 billion, cumulatively, the twenty-four financial firms in our sample gained $32.61 billion. These results clearly show that China’s financial firms welcomed the Trump tariff cancellations.